Supporting biodiversity studies with the EUBrazilOpenBio Hybrid Data Infrastructure. (12th March 2014) - Amaral, Rafael; Badia, Rosa M.; Blanquer, Ignacio; Braga‐Neto, Ricardo; Candela, Leonardo; Castelli, Donatella; Flann, Christina; De Giovanni, Renato; Gray, William A.; Jones, Andrew; Lezzi, Daniele; Pagano, Pasquale; et al.
Summary EUBrazilOpenBio is a collaborative initiative addressing strategic barriers in biodiversity research by integrating open access data and user‐friendly tools widely available in Brazil and Europe. The project deploys the EU‐Brazil Hybrid Data Infrastructure that allows the sharing of hardware, software and data on‐demand. This infrastructure provides access to several integrated services and resources to seamlessly aggregate taxonomic, biodiversity and climate data, used by processing services implementing checklist cross‐mapping and ecological niche modelling. A Virtual Research Environment was created to provide users with a single entry point to processing and data resources. This article describes the architecture, demonstration use cases and some experimental results and validation. Copyright © 2014 John Wiley & Sons, Ltd.